Chlorine or Chloramine for Drinking Water Disinfection? A Case Study of a New Decision Framework - Fisher, I.; Kastl, G.; Fayle, B.; Sathasivan, Arumugam (Cambridge Scientific Abstracts, 2009)
Chlorine and chloramine are the two most widely used disinfectants in drinking water distribution systems. A new framework is proposed, within which the choice between their use is based on the ability of each to achieve specified performance goals within the system of interest. While prediction of chlorine performance can be made with available state-of-the-art chlorine decay modelling, the same cannot yet be achieved for chloramine performance. This approach is demonstrated in a case study where performance of the current chloramination of a distribution system was compared with the modelled performance of chlorination. As work progresses on understanding the development of chloramine-decaying microorganisms, it is anticipated that choice will be based on the performance of each option, as simulated by EPANET and MSX-based network models, such as H2ONET.